Development of alpha-lipoic acid encapsulated chitosan monodispersed particles using an electrospray system: synthesis, characterisations and anti-inflammatory evaluations. (1st April 2014) - Bai, Meng-Yi; Hu, Yao-Ming
Abstract: This study demonstrates the feasibility of using a single-capillary electrospray (ES) system to generate novel alpha-lipoic acid encapsulated poly(ethylene oxide)–chitosan (ALA/PEO/CS) particles with a monodispersed diameter. Scanning electron microscopic images (SEM) and dynamic light scattering (DLS) results indicate that the ES system can generate either a dry powder or a homogeneous water-based suspension of ALA/PEO/CS particles. The SEM images revealed that the ALA/PEO/CS particles have a spherical shape with a diameter of approximately 707 ± 66.68 nm, and DLS showed that the ALA/PEO/CS particles suspended in deionised water have a diameter of 734.5 nm. In addition, zeta potential studies were performed using a zetasizer instrument and showed positively electric surface potential of 57.7 ± 0.5 mV, which was attributed to chitosan. Based on the DLS and zeta potential studies, we concluded that the excellent dispersity and stability of the ALA/PEO/CS suspension is attributed to the reduction in particle size and electrostatic repulsion between these tiny particles. Finally, we used lipopolysaccharide (LPS)-induced nitrite formation in Raw 264.7 macrophages as a model for in vitro anti-inflammation evaluation. We find that the anti-inflammatory ability of the ALA/PEO/CS particles is superior to that of free ALA solution in macrophage cells, which is attributed to the more efficiently intracellular delivery. The confocal image results prove that the uptake of ALA/PEO/CS particles by the LPS-treated Raw 264.7 macrophages is possibly initiated by the interaction with cell-surface molecules through electrostatic interactions, followed by endocytosis of the attached particles.